PENGEMBANGAN MEDIA PEMBELAJARAN FLASHCARD PADA TEMA PEDULI LINGKUNGAN SOSIAL RA MUSLIMAT NU BUKO DEMAK - Anis Rahmawati; Umi Faizah (STPI Bina Insan Mulia Yogyakarta, 2024)
Media is very important to use because the learning media can convey or distribute messages from a source in a planned manner so that a conducive learning environment, where the recipient can make the learning process efficiently and effectively. This development research aims to Know the development procedure of learning media flashcard, know the feasibility of flashcard learning media developed. The type of this research is development research using ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. This study produces flashcard media as a learning resource that can facilitate learners in order to play an active role, and make it easy for learners in understanding the theme 4 care about the social environment. The results showed that flashcard learning media is feasible to be tested without revision based on final validation results that have been done by media experts who claimed to be tested with a 90% validity level and material experts stated that it is feasible to be tested with a 94% level of validity. Based on the results of practicality that has been done with the test in the classroom and interview results obtained the result that the flashcard media developed to attract the attention of learners so that they can understand the learning materials on the theme of social care environment class III RA Muslimat buko Wedung.